2006
DOI: 10.1080/00016480600794453
|View full text |Cite
|
Sign up to set email alerts
|

The role of SPECT-CT in the lymphoscintigraphic identification of sentinel nodes in patients with oral cancer

Abstract: SNB was conducted in 33 patients. SNs were identified in 94% (32/34) of the patients using SPECT-CT. In 91% (29/32) of the patients SNs were harvested from all of the levels involved on SPECT-CT. SPECT-CT imaging demonstrated extra SNs compared with planar lymphoscintigraphic imaging in 47% (15/32) of patients. In seven cases the anatomical level of SN according to SPECT-CT was reclassified during surgery. The overall incidence of lymph node metastases was 19% (6/32). There were no false negative SNs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 23 publications
4
55
0
1
Order By: Relevance
“…In general, more SNs are identified by SPECT/CT than by planar lymphoscintigraphy (16)(17)(18)(19)(20). However, it may remain difficult or impossible to establish which are true SNs rather than second-echelon ones.…”
Section: Discussionmentioning
confidence: 99%
“…In general, more SNs are identified by SPECT/CT than by planar lymphoscintigraphy (16)(17)(18)(19)(20). However, it may remain difficult or impossible to establish which are true SNs rather than second-echelon ones.…”
Section: Discussionmentioning
confidence: 99%
“…Because of complex lymph drainage systems and the presence of several vital structures such as vessels and nerves, preoperative imaging in this region is essential. Several authors have concluded that the additional use of SPECT/CT in head and neck cancer leads to detection of more sentinel nodes and better anatomic localization of the sentinel nodes (12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Besides breast cancer, the use of SPECT/CT has been quite well described in sentinel node lymphadenectomy for head and neck cancer (12)(13)(14)(15)(16)(17). Because of complex lymph drainage systems and the presence of several vital structures such as vessels and nerves, preoperative imaging in this region is essential.…”
Section: Discussionmentioning
confidence: 99%
“…SPECT/CT has been reported to visualize additional sentinel nodes in this anatomically complex area [31,36,39,[41][42][43]. Sentinel nodes located in the vicinity of the injection site are easily missed on the conventional images and can often be discerned using SPECT/CT [36,37].…”
Section: Spect/ct In Patients With Other Malignanciesmentioning
confidence: 99%
“…Various authors describe that SPECT/CT provides useful information as to the exact location of sentinel nodes in head and neck malignancies [31,34,36,37,[39][40][41], as is exemplified in Figure 3. SPECT/CT has been reported to visualize additional sentinel nodes in this anatomically complex area [31,36,39,[41][42][43].…”
Section: Spect/ct In Patients With Other Malignanciesmentioning
confidence: 99%